Self-Rated Health among General Population in the West of Iran: A Cross-Sectional Analysis of Socioeconomic Determinants (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Self-rated health (SRH), as a powerful independent predictor of mortality, has been used worldwide.However, there is currently lack of information about the SRH in Iran as a developing country. This study was conductedto investigate the relationship between SRH and socioeconomic factors in the general population in western Iran.Methods: A cross-sectional study was conducted in 2017 enrolling 1,444 subjects aged 18 years and over in fiveareas of Kermanshah City, Iran. A single question of SRH with five scales of excellent (coded as 1), very good, good,fair, or poor (coded as 5) was used. Univariate and multiple logistic regression models were performed to determinefactors associated with poor self-rated health.Results: The proportion of poor SRH was 14.7%. Multiple logistic regression showed that the most importantdeterminants of poor SRH were older age (adjusted odds ratio (AOR)31-50year=1.96, AOR≥51year=4.93, married status(AOR=2.53), divorced or widowed status (AOR=2.62), self-reported income level as middle (AOR=2.51) andlow (AOR=4.59), rural residency (AOR=1.5), low physical activity (AOR=11.97), and having chronic diseases(AOR=6.85). In addition, the educational level had a negative relationship with poor SRH (AOR academic=0.47).Conclusion: Our results revealed that both individual and social factors are directly associated with poor SRH.Therefore, these determinant factors should be considered in health policies and planning for promoting health andSRH in the west of Iran.
Keywords: Self-rated health; Heath status; Cross-sectional study